The Influence of Board Remuneration, Multiple Large Shareholders, and Insider CEOs on ESG Disclosure - Fauzi, Alisha Rasiyah; Hasnawati, Hasnawati (Dinasti International Journal of Management Science, 2026)
Transparency in environmental, social, and governance (ESG) aspects within Indonesia's energy sector remains varied despite high environmental risks. This study aims to analyze the effect of board remuneration, multiple large shareholders, and insider CEOs on ESG disclosure. This study employs a quantitative approach using unbalanced panel data from 44 energy sector companies listed on the Indonesia Stock Exchange from 2022 to 2024. Data analysis was conducted using panel data regression with the Random Effect Model. The results indicate that board remuneration and the presence of multiple large shareholders have a significant positive effect on ESG disclosure. Conversely, the insider CEO status was not proven to significantly affect the level of sustainability disclosure. Additionally, profitability was found to be a crucial prerequisite for transparency, whereas capital structure had no meaningful impact. The study concludes that structural governance mechanisms through financial incentives and shareholder monitoring are more dominant in driving sustainability accountability compared to executive background characteristics